DMT: A model detecting multispecies of tea buds in multi-seasons - Yu, Taojie; Chen, Jianneng; Chen, Zhiwei; Li, Yatao; Tong, Junhua; Du, Xiaoqiang (International Journal of Agricultural and Biological Engineering, 2024)
In China, tea products made from fresh leaves characterized by one leaf with one bud (1L1B) are classified as “Famous Tea”, which has better taste and higher economic value, but suffers from a labor shortage. Aiming at picking automation, existing studies focus on visual detection of 1L1B, but algorithm validation is limited to a specific variety of tea sprouting in a certain harvest season at a certain location, which limits the engineering application of developed tea picking robots working in various natural tea fields. To address this gap, a deep learning model DMT (detecting multispecies of tea) based on YOLOX-S was proposed in this paper. The DMT network takes YOLOX-S as a baseline and adds ECA-Net to the CSP Darknet and FPN of YOLOX-S. The average precision (AP), precision, and recall of DMT are 94.23%, 93.39%, and 88.02%, respectively, for detecting 1L1B sprouting in spring; 93.92%, 93.56%, and 87.88%, respectively, for detecting 1L1Bsprouting in autumn. These experimental results are better than those of the five current object detection models. After fine-tuning the DMT network with another dataset composed of multiple tea varieties, the DMT network can detect 1L1B for different varieties of tea in multiple picking seasons. The results can promote the engineering application of picking automation of fresh tea leaves. Keywords: tea buds, detection model, multispecies of tea, multi-season DOI: 10.25165/j.ijabe.20241701.8021 Citation: Yu T J, Chen J N, Chen Z W, Li Y T, Tong J H, Du X Q. DMT: A model detecting multispecies of tea buds in multi-seasons. Int J Agric & Biol Eng, 2024; 17(1): 199-208.